Some core concepts of domain analysis - Birger Hjørland (Em Questão)
This article claims that information systems should provide reliable and trustworthy information, and that this demand imply a re-orientation of information science with knowledge organization from, for example, approaches based on studies of user’s preferences, towards studies of quality and the values and goals in the documents being mediated. This mediation is done by information professionals in their knowledge organization systems and –processes. For this purposes, the philosophy of science becomes an important subject, which has implications for the understanding of a longrange of concepts. Here, the following concepts are briefly introduced: “social epistemology”, “information”, “question,” “relevance,” “information need,” “concept,” and “subject” (of documents).